Ubuntu as grounding principle in pursuit of academic freedom, institutional autonomy, and public accountability for African universities - Radebe, N. (South African Journal of Higher Education, 2025)
The attempts to transform universities in South Africa have focused on the discourse of academic freedom, institutional autonomy and public accountability as enablers of transformation. As such, academic freedom, institutional autonomy and public accountability are about redressing past injustices because the legacy of the past has implications within the context of the democratisation and transformation of higher education in South Africa. However, there is not enough focus on knowledge production, which is critical in the transformation of universities such that scholars are at liberty to draw from the well of knowledge from where they are standing without being hamstrung by already existing theories and concepts to seek validation. The article argues that African philosophies have a critical role to play in the transformation of universities. It therefore uses the philosophy of ubuntu as an example to show the ethical existence of African people that should anchor African universities to reflect the ethos of the communities they serve. Ubuntu thus provides a possibility for universities to cease being ivory towers and begin to forge a symbiotic relationship with their communities. This shows the importance of universities learning from communities and, in turn, using such learnt knowledge to develop theories that solve societal problems before that knowledge is transported to solve the world’s challenges. Universities in Africa must therefore become true to African epistemologies where thinkers think from and for communities. The article concludes by arguing that academic freedom, institutional autonomy and public accountability should be anchored in ubuntu to produce graduates that will be of service to humanity.